The theological basis of the social commitment of San Alberto Hurtado (2010)
San Alberto Hurtado (1901-1952) is known for his commitment to the poorest and working to achieve social justice. However, the purpose of this paper is not a description of his works, but rather an insight to his theological basis. A research based on his writings, including an extensive database of unpublished manuscripts, allows to acknowledge a solid theological and spiritual foundation for his social commitment: his concept of God, the theology of the Mystical Body of Christ and his convictions on dignity of man, called to eternal life, are the elements that provide foundation, strength and meaning to his social commitment. Furthermore, they attest that it is impossible to understand Saint Alberto's action without bearing in mind his faith convictions. Thus, as he states, spiritual life and social commitment do not oppose each other: «Our spiritual life not only does not exclude a social attitude, but rather urges it».